Racism: An American Cauldron - Doob, Christopher Bates (HarperCollinsCollege, 1996)
Keywords: Race relations; Racism; United States; United States; dept.soc; faculty_collection

Trial by plea bargain: Case settlement as a product of recursive decisionmaking - Emmelman, DS (Law & Society Review, 1996)
Through presentation of ethnographic research findings on court-appointed defense attorneys, this article examines plea bargaining as a component of a recursive process for deciding whether a case should be settled immediately or proceed further. The decisionmaking process has three types of activities: assessing the offer for a guilty plea, negotiating the terms of a plea bargain, and counseling the defendant and deciding on a course of action. Until a criminal case is actually settled either through a final plea agreement or a jury trial, this decisionmaking process occurs over and over again. Viewed as a component of this recursive process, plea bargaining encompasses multiple episodes of negotiating behavior as well as a wide range of formal litigation proceedings. Perhaps more important, plea bargaining and trial procedures can actually be seen to converge. I conclude that this mode of plea bargaining is not merely an effective method for representing defendants but perhaps equally or more effective than trial. Some important limitations of the findings are also discussed.
31 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1996UX39800005
Keywords: dept.soc